Finlandiya’nın pısa başarısına etki eden faktörler bağlamında Türkiye’nin durumu - Yıldız, Ali (My University, 2013)
FİNLANDİYA’NIN PISA BAŞARISINA ETKİ EDEN FAKTÖRLER BAĞLAMINDA TÜRKİYE’NİN DURUMU Finlandiya ve Türkiye’nin bağımsız devlet oluşu birbirine yakın zamanlarda gerçekleşmiştir. Finlandiya 1917, Türkiye ise 1920’de bağımsızlığını ilan etmiştir. Bu bakımdan her iki ülkenin de hikâyelerinde farklılıklar kadar benzerlikler de bulunmaktadır. 1920’lerde hem Finlandiya hem Türkiye sanayileşmenin henüz başlamadığı birer tarım ve hayvancılık ülkesi konumundaydı. İki ülkede de eğitimli insan sayısı çok az, ülke sathında okullaşma oranı çok düşüktü. Bu bakımdan iki ülkede de eğitim sektörünün gelişmesine yönelik büyük çabalar sarf edildi. Ancak bu çabalar sonunda, Türkiye’yle karşılaştırıldığında Finlandiya daha çok yol aldı. Bugün Finlandiya ekonomik bakımından çoktan refah toplumu aşamasına geçmişken, Türkiye henüz gelişmekte olan ülkeler içinde yer almaktadır. Neredeyse bütün uluslararası göstergelerde Finlandiya en iyi on içinde yer almaktadır. Finlandiyalılar bu durumlarını eğitime yaptıkları yatırımlara bağlamaktadır. Örneğin şu ana kadar yapılan bütün PISA sınavlarında Finlandiya son derece başarılı sonuçlar almıştır. Bu özelliğiyle Finlandiya çok sayıda ülkenin dikkatini çekmiştir. Bu ülkelerden biri de Türkiye’dir. Katıldığı bütün PISA sınavlarında oldukça başarısız sonuçlar alan Türkiye’nin bu başarısızlığını anlamak için Finlandiya’nın başarısında etkin olan başat faktörlerin ayrıntılı bir analizinin yapılması gerekmektedir. İşte bu çalışma büyük oranda bunu amaçlamıştır. Kısaca, bu çalışmayla, Finlandiya’nın PISA başarısına etki eden faktörler bağlamında Türkiye’nin durumu saptanmaya çalışılmıştır. Bu amaç doğrultusunda araştırmanın problem cümlesi, Finlandiya’nın PISA başarısına etki eden faktörler bağlamında, Türkiye’nin PISA sınavlarında yaşadığı başarısızlık nasıl açıklanabilir?, şeklinde belirlenirken, alt problemleri ise şu şekilde ortaya çıkmıştır: oBir süreç olarak öğretmen eğitimi Türkiye’de nasıl gerçekleşmektedir? oEğitim öznesi olarak öğretmen ve idareciler Türk Eğitim Sistemi’nde ne ölçüde etkilidir? oEğitim ortamı olarak okulların kalitesi Türkiye’de eğitimin niteliğine nasıl etki etmektedir? Öte yandan, araştırma sonunda bir kısım bulgulara ulaşılmıştır. Ulaşılan bu bulgulardan yola çıkılarak hem araştırmacılara hem de uygulayıcılara yönelik bazı öneriler oluşturuldu. Araştırma sonucunda ulaşılan bulgular kısaca şu şekilde özetlenebilir: Katılımcılar büyük oranda öğretmen profesyonelliği kavramın literatürdeki karşılığı konusunda habersiz, ancak bir şekilde bu kavramın kullanılmasından da tedirgin görünmektedir. Bununla birlikte, profesyonelliğin önünde pek çok engel sayılmakla birlikte en dikkat çeken unsur ekonomik gerekçeler olarak ortaya çıkmaktadır. Çözüm olarak, yüksek lisans çalışmaları, araştırmacı öğretmen nitelikleri, kişisel gelişim planı ve sürekli eğitim ile öğretmen ve idarecilerin/ yöneticilerin profesyonelliklerini en üst düzeyde yaşamları önerilmektedir. Öte taraftan, eğitim fakültelerinde eğitim, kuram ağırlıklı olup, staj formaliteden ibaret görünmektedir. Hâlbuki staj süresi ile aday öğretmenlik sürecinin çok iyi değerlendirilmesi gerekmektedir. Bu sorun Finlandiya’da büyük bir oranda uygulama okulları kanalıyla aşılmıştır. Dahası, Türkiye’de eğitim fakültelerinden mezun olan öğretmenlerin neredeyse hiçbiri tek başına araştırma yapacak kapasiteye sahip olmadığı gibi, bu konuda istekli de görünmemektedir. Ancak çağımızın eğitim yaşantısı öğretmenlerin bu niteliğe sahip olmasını zorunlu kılmaktadır. Öğretmen ve idarecilerle yapılan görüşmelerden eğitimin daha çok sınıf içi bir etkinlik olarak görüldüğü, öğretmenlerin müfredat dışı etkinlikler ve alternatif yöntemler kullanma konusunda isteksiz ve çekingen davrandığı sonuçlarına ulaşılmıştır. Ayrıca, katılımcılar öğrencilerin, hatta öğretmenlerin bile ilgi ve isteklerinin ders programlarına yansıtılamadığını, dolayısıyla da bir şekilde öğretmen ve öğrencilerin eğitim dışı bir unsur gibi görüldüğünü dile getirmiştir. Bu arada sınav konusunda ebeveynlerin öğretmenlere olan güveni henüz çok sarsılmamış görünmekle birlikte, öğretmen ve idareciler bile kendi hazırladıkları sınavların yetersizliğinden söz etmektedir. Daha da kötüsü, okulda gerçekleştirilen her türlü yeniliğe karşı önemli ölçüde mukavemet yaşanmaktadır. Bu direnme büyük oranda daha kıdemli öğretmenlerden kaynaklansa da, hemen hemen hiçbir öğretmen ve idareci yenilikleri uygulama konusunda çok istekli görünmemektedir. Hâlbuki Finlandiya’da öğretmen eğitimi araştırma temelli olduğu ve bilginin de temelinin dinamik olması gerektiğinden, onlarda yeniliklere karşı isteksizlik bu ölçüde yaşanmamaktadır. İlginçtir, Türkiye’de öğretmen ve idarecilerin tamamına yakını öğrenmeyi hala davranışçı açıdan görmektedir. Buna bağlı olarak öğrenciler arasında ezberlemeye dayalı öğrenme yaklaşımı bir hayli popülerdir. Pek çok katılımcıya göre, okullarda verilen ödüllerin pedagojik bakımdan çok büyük bir anlamı yoktur. Öğrenciler maddi ödülleri daha çok takdir etmektedir. Bunun yanı sıra, okullarda mevcut rehberlik hizmetleri kadük duruma düşmüştür. Bu bakımdan çağın ihtiyaçlarına yanıt verebilecek yeni bir danışmalık birimine ihtiyaç duyulmaktadır. Diğer taraftan katılımcıların büyük çoğunluğu

denetim/ öz değerlendirme, iç ve dış denetim gibi trend kavramlara olumlu bakmakla birlikte, bunların okullarımızda uygulanması konusunda bir ölçüde karşı ya da gönülsüz görünmektedir. Buradaki temel çıkmaz güvensizlik gibi görünmektedir. Son bir bulgu olarak Finlilerin, ders ya da sınıflarında arkadaşlarından geride kalan öğrencilere daimi bir desteğin verilmesi anlamına gelen “remedial teaching” yaklaşımına destek veren görüşülenlerin büyük bir çoğunluğu (%75), ancak bunun nasıl yapılacağı konusunda tereddütlü görünmektedir. Hâlbuki bu, Finlandiya’da anayasal bir hak olarak yer almakta ve son derece sistematik bir biçimde uygulanmaktadır. Ayrıca Finliler bu uygulamadan gurur duyduklarını belirtmektedir. Zira PISA sınavlarında Finli öğrenciler Güney Kore ile birlikte en düşük başarısız öğrenci oranına sahiptir (% 7 civarında). Bu arada PISA sınavlarına giren Türk öğrencilerin ortalama % 60 kadarı 6’lı skalada (gösterge çizelgesi) ancak 2 ve 2’nin altında yer alarak başarısız olmuştur. Kısaca, Finlandiya ve Türkiye’nin PISA sınavlarında elde ettiği sonuçların karşılaştırıldığı bu çalışmada, Finlandiyalıların ne yaptıklarından daha emin ve kararlı göründüğü söylenebilir. Ayrıca Finlandiyalılar eğitim gibi toplumsal bir konuda Türkiye ile kıyaslanmayacak ölçüde çabuk uzlaşmaya varmaktadır. Yani, eğitim Finlandiya’da siyaset üstü bir konu olarak değerlendirilmektedir. Anahtar Sözcükler: Finlandiya Eğitim Sistemi, Türk Eğitim Sistemi, Öğretmen Eğitimi, PISA, Başarı Faktörleri. ABSTRACT TURKEY’S SITUATION IN THE CONTEXT OF THE FACTORS AFFECTING FINLAND’S PISA SUCCESS In this study, the first step of purpose was to explore what factors most affect the success of Finnish students in OECD’s PISA exams. Then, we have reached some outcomes by evaluating the situation of Turkey in all PISA exams in the context of these factors. In the last years, the numbers of the countries comparing themselves with Finland have been increasing day by day. Because, Finland is one of the top countries in all PISA exams. Nearly all countries want to learn the reasons behind the Finnish success in PISA exams. Although everbody sees a lot of factors behind this, in fact, some factors like teachers, teacher education and schools are seen as the most dominant ones in Finland’s PISA success. For this, the study which compares the results of Finland and Turkey in PISA focuses on these three factors. So, this study addresses the following research question and three sub-questions: •How can it be explained Turkey’s failure in PISA exams in the context of the factors affecting Finland’s success in the same international Project? oHow is the teacher education as a process implemented in Turkey? oHow effective are the teachers and administrators as education agents in Turkish eduaction system? oHow does the quality of schools as a place of education affect the quality of eduaction in Turkey? On the other hand, the sample of the study consists of 20 teachers and administrators in Avcılar county in the city of Istanbul. While selecting the interviewees, the approach of purposeful sampling was used because of the fact that our semi-structured questions can only be effective with the sophisticated and qualifed interviewees. During the in-depth interview, 15 semi-structured questions were asked to the interviewees and their answers were recorded by the help of a MP3 player. Then, these sound records were transformed into a written text. Finally, all the data on the papers were analysed by the help of the content analysis. By the way, the questions used in interview were chosen from a question pool under the supervision of an expert. There were lots of findings some of which are quite important were derived from the reserarch. Some of those findings of this research can be stated as follows: Although the interviewees are not mostly seen aware of the concepts related to teacher professionalism, they are sensitive about the use of such kinds of terms in education. Meanwhile, interviewees see the economical condition as the most important handicap for professinal improvement. To overcome such handicaps, economical or not, teachers and administrators should make a personal improvement plan. On the other, eduaction in Turkish teacher education departments are mostly theory-based, and there are a lot of problems in internship period. For this reason, teachers have to pay more attention to the internship period in particular. This problem is solved by the help of the laboratory schools in Finland. Furthermore, when the teacher candidates graduate from the faculty of education in Turkey, few of them can be seen as elligible for the vacant position in schools. Because, they have lots of deficiencies in their pedagogical and field knowledges. In our schools, it seems that teachers are unwilling to use alternative methods in their lessons. They are inclined to use their old methods in general. Also, they limit the learning process with the class, and they do not want to do anything out of the classroom. Moreover, neither students nor teachers are inside the education. According to some of the interviewees, our formal education system does not really include all. Meanwhile, parents and other shareholders do not trust teachers anymore. There is a lack of confidence among teachers and others. In addition, there is too much resistance toward improvements in schools. Although much of the resistance comes form relatively veteran teachers and administrators, other teachers and administrators are also reluctant to be in confirmity with the improvements. Whereas, the Finnish teachers do not resist on the improvement so much because of the fact that in Finland teacher eduaction is research-based, and so teachers are familiar to every kinds of improvements. It is very interesting to say that teachers and administrators still believe and explain the learning concept as from the behaviouristic approach. It is very popular in our schools and classes. So, students are accustomed to learning by heart at schools. To some interviewees, there are a lot of awards in our schools, but they are not attractive for students. Because students generally want to be awarded with a material not something moral. They generally appreciate for the material awards. There are some other problems in our schools, too. For example, counselling services in our schools are not effective nowadays. For this, schools need a new type of counselling services. One of the other problems is that most of the interviewees have positive ideas about the new concepts, such as self assessment, external or internal evaluation. But they think that there are a lot of obstacles for such kinds of evaluation in our schools and society. As it is stated previously, there is the same problem among the shareholders of education. This problem is also the lack of confidence. On the other, there is a kind of special teaching known as “remedial teaching” among Finnish people. In these teaching activities, the students who feel weak in any subjects can attend these courses under the supervision of the teachers that are experts in special education. Such a teaching is generally supported by Turkish teachers and administrators, but it is found unpracticle to use it in Turkish schools. Perhaps it can help the weak students who fall behind the other students in the class. Whereas, it is a constitutional right for every pupil in Finland. Furthermore, Finnish people are content to have such a useful implementation in their schools. That’is why, Finland with South Korea have the lowest proportion of the weak students in PISA exams (about 6-7 %). Finally, when Finland and Turkey are compared in the context of the PISA outcomes, it can clearly be seen that Finnish people and schools are much more confident and determined about what they want to do or to be than us. Above all, Finnish people are always ready to solve any problems related to education or education system. Key Words: Finnish Education System, Turkish Education System, Teacher Education, PISA, Factors affecting PISA Success.
Keywords: Eğitim; Eğitim Testleri ve Ölçümleri; Fillandiya; Türkiye